A Note on Hierarchy and Coordination: An Aspect of Decentralization - Kochen, Manfred; Deutsch, Karl W. (Management Science, 1974)
A mathematical expression for the cost of maintaining a client-centered service organisation is derived. It shows the dependency of the total cost on the service-request load, the number of hierarchical levels of the organization, and the administrative costs. The mathematical formulation is based on a model in which the main variables are the times spent on communication between different levels of the organisation and on communication between agents at the same level. The optimum number of levels for minimising cost is derived, and its sentivity to request load is investigated.